The essence and significance of environmental modernization of enterprises - Savko O.; Савко О.; Gobyr I.; Гобир І. (ФОП Сабов А. М., 2019)
Abstract. In modern conditions, environmental problems, in particular, related to climate changes, have become priority problems that threaten human development. Ukraine, as a member of the United Nations Framework Convention on Climate Change (1992), took on international obligations defined by the Kyoto Protocol (1997), and the Paris Agreement (2015) to reduce greenhouse gas emissions. This requires from our state forming and implementing an effective environmental policy, which should be built on the basis of the concept of environmental modernization, which began to develop as an interdisciplinary branch from the 70s to 80s of the 20th century.
Сутність та значення екологічної модернізації підприємств
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00007679
Keywords: environmental modernization; enterprise